Immunoreactive Atrial Natriuretic-like Peptide in Antarctic Teleosts - B. Uva; MASINI, MARIA ANGELA; L. Napoli; M. Devecchi (Comparative Biochemistry and Physiology Part A: Physiology, 1993)
1. 1. The presence of an atrial natriuretic-like peptide (ANP) has been investigated in the Antarctic fish Chionodraco hamatus (Channichthydae) and Pagothenia bernacchii (Notothenidae). 2. 2. By radioimmunoassay an ANP-like peptide has been detected in plasma and heart homogenates of both white blooded (Chionodraco) and red blooded (Pagothenia) species. 3. 3. By immunohistochemistry atrial nutriuretic factor (ANF) immunoreactive cardiocytes have been demonstrated in the atria of Chionodraco and Pagothenia using Ab to rat 99–126 ANF. Ventricular immunoreactivity is absent in both species. 4. 4. ANP binding sites have been visualized by autoradiography in the kidney, gills and heart of both Pagothenia and Chionodraco. 5. 5. Our data indicate that ANP concentration is greater in the white blooded than in the red blooded fish.